A novel acropectoral syndrome maps to chromosome 7q36. Issue 5 (1st May 2001) - Dundar, Munis; Gordon, Tilda M; Ozyazgan, Irfan; Oguzkaya, Fahri; Ozkul, Yusuf; Cooke, Alexander; Wilkinson, A Graham; Holloway, Susan; Goodman, Frances R; Tolmie, John L
Abstract : F syndrome (acropectorovertebral syndrome) is a dominantly inherited skeletal dysplasia affecting the hands, feet, sternum, and lumbosacral spine, which has previously been described in only two families. Here we report a six generation Turkish family with a related but distinct dominantly inherited acropectoral syndrome. All 22 affected subjects have soft tissue syndactyly of all fingers and all toes and 14 also have preaxial polydactyly of the hands and/or feet. In addition, 14 have a prominent upper sternum and/or a blind ending, inverted U shaped sinus in the anterior chest wall. Linkage studies and haplotype analysis carried out in 16 affected and nine unaffected members of this family showed that the underlying locus maps to a 6.4 cM interval on chromosome 7q36, between EN2 and D7S2423, a region to which a locus for preaxial polydactyly and triphalangeal thumb-polysyndactyly has previously been mapped. Our findings expand the range of phenotypes associated with this locus to include total soft tissue syndactyly and sternal deformity, and suggest that F syndrome may be another manifestation of the same genetic entity. In mice, ectopic expression of the gene Sonic hedgehog ( Shh ) in limb buds and lateral plate mesoderm during development causes preaxial polydactyly and sternal defects respectively, suggesting that misregulation of SHH may underlie the unusual combination of abnormalities in this family. A recently proposed candidate gene for 7q36 linked preaxial polydactyly is LMBR1, encoding a novel transmembrane receptor which may be an upstream regulator of SHH .